(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
The article provides information on virtual and 3D teaching technologies, V-academia, simulators used to teach chemistry in the education system, and the application of simulators to the teaching process. Educational institutions also discuss 3D modeling, 3D scanning, ideas on the importance of 3D printing drawings in improving the quality of the learning process in chemistry education, and its application in chemistry education.